An overview of risk factors associated to post-partum depression in Asia - Shubham Mehta; Nidhi Mehta (Mental Illness)
Post partum depression (PPD) is an important complication of child-bearing. It requires urgent interventions as it can have long-term adverse consequences if ignored, for both mother and child. If PPD has to be prevented by a public health intervention, the recognition and timely identification of its risk factors is must. We in this review have tried to synthesize the results of Asian studies examining the risk factors of PPD. Some risk factors, which are unique to Asian culture, have also been identified and discussed. We emphasize on early identification of these risk factors as most of these are modifiable and this can have significant implications in prevention of emergence of post partum depression, a serious health issue of Asian women.